Analysis of the safety and efficacy of PD-1/PD-L1 inhibitors combined with chemotherapy in the treatment of locally advanced resectable esophageal squamous cell carcinoma: a systematic review and meta-analysis based on four randomized controlled trials - Luo, Tao; Yang, Hao; Ran, Xingqiang; Xu, Binwen; Zhang, Yue; Zhang, Liwen; Zhang, Chengcheng; Fu, Maoyong (Frontiers in Oncology, 2025)
BackgroundEsophageal cancer is a leading type of cancer globally. Most patients diagnosed with esophageal cancer present at a locally advanced stage, for which the standard treatment paradigm involves a multimodal approach combining neoadjuvant therapy with surgical resection. However, even under this regimen, 30%–40% of patients develop distant metastases postoperatively. This underscores an urgent need to refine existing therapeutic strategies and develop innovative multimodal protocols to address persistent oncological challenges in this high-risk population. In recent years, the advent of immunotherapy has expanded its application from advanced to early-stage settings, with neoadjuvant immunotherapy gaining traction in the management of locally advanced esophageal cancer. However, critical uncertainties persist regarding its preoperative use. This study aims to conduct a meta-analysis comparing the efficacy and safety of neoadjuvant chemoimmunotherapy (nICT) versus conventional neoadjuvant chemotherapy (nCT) in this patient population.MethodsA comprehensive literature retrieval strategy was implemented across PubMed (NLM), Embase (Elsevier), and the Cochrane Central Register of Controlled Trials, targeting studies published prior to December 2024 that compared novel immunochemotherapy (nICT) with conventional nCT in locoregionally advanced esophageal carcinoma. Pooled statistical analysis of the eligible randomized controlled trials (RCTs) was subsequently conducted to evaluate comparative safety and efficacy profiles.ResultsThe final analysis incorporated four randomized controlled trials (RCTs) comprising a total cohort of 629 participants. Patients receiving nICT for locoregionally advanced esophageal carcinoma demonstrated significantly prolonged intervals between final preoperative treatment and definitive surgical resection when compared to those undergoing conventional nCT alone [weighted mean difference (WMD): 0.71 weeks; 95% confidence interval (CI) 0.39–1.02; P < 0.0001]. The combined treatment showed significant advantages in pathological complete response (PCR) [odds ratio (OR): 3.44; 95% CI 1.98–5.97; P < 0.0001] and major pathological response (MPR) (OR: 2.56; 95% CI 1.23–5.30; P = 0.01). However, the incidence of anemia as an adverse reaction was higher in the combined treatment group (OR: 1.83; 95% CI 1.08–3.09; P = 0.02).ConclusionNeoadjuvant chemotherapy combined with immunotherapy for treating locally advanced esophageal cancer is effective and safe. However, due to the absence of long-term follow-up data, additional large-scale, multicenter randomized controlled trials are required to confirm these results.